Unrevealing the Hidden Effects of Job Insecurity: A Moderated-Mediation Model of Moral Disengagement and Moral Identity - Zhang, Zheng; Waqas, Muhammad; Yahya, Farzan; Qadri, Usman A.; Marfoh, Joseph (Frontiers in Psychology, 2022)
Moral disengagement is an intensely negative reaction that triggers unethical behavior in the workplace. By integrating the conservation of resources and moral disengagement theories, the current research examined how moral disengagement can explain the mechanism through which job insecurity results in adverse consequences. Furthermore, moral identity was theorized to moderate the hypothesized relationships. The theoretical model was tested by using time-lagged multisource data was collected from 425 Chinese employees and their respective supervisors associated with the healthcare sector. The study concluded that job insecurity was positively linked with employees’ moral disengagement, which, in turn, led to coworker undermining behavior. Furthermore, moral identity moderated the relationship between job insecurity, moral disengagement, and coworker undermining such that employees high in moral identity experience less moral disengagement and are less involved in coworker undermining. Theoretical and practical implications along with future research avenues are discussed.